Neuronal circuits underlying learning of competing action strategies - Vicente, Ana Mafalda dos Reis de Abreu Rodrigues (2019)
The nervous system is an amazing adaptation that allows animals to react to (and act on) their perception of the environment. One extremely important feature of an organism is the capacity to learn new actions upon exposure to new contexts, situations or necessities. When an action begins to be learned, the behaviour is highly dependent on the expected value of the outcome associated with it. However, with repetition, the execution of an action can become less dependent on the value of its consequences, and progress to a habit. Habitual behaviour is, in general, characterized by the relative independence from the outcome, and seen instead as a stimulus-response association. Several studies have pinpointed that these two behavioural modes depend on dissociable circuits in the brain, with dorsomedial striatum and basolateral amygdala involved in goal-directed actions, and dorsolateral striatum involved in habits. Nevertheless, little is known about their interaction during action learning, or how the system balances both modes during the behaviour output. Furthermore, dopamine, which is an important neuromodulator, has also been associated with this process. Accordingly, dopamine depletion in dorsolateral striatum leads to increased sensitivity to changes in the value of the outcome.